Five years of post-validation surveillance of lymphatic filariasis in Thailand - Prapapan Meetham; Rawadee Kumlert; Deyer Gopinath; Siriporn Yongchaitrakul; Tanaporn Tootong; Sunsanee Rojanapanus; Chantana Padungtod (BMC, 2023)
Abstract Background The World Health Organization (WHO) validated Thailand in 2017 as having eliminated lymphatic filariasis (LF) as a public health problem with recommendations for continued surveillance. This article describes measures and progress made in Thailand with post-validation surveillance (PVS) of LF from 2018 until 2022. Methods The implementation unit (IU) is a sub-village in 11 former LF endemic provinces. Human blood surveys are targeted in 10% of IUs each year. In Wuchereria bancrofti areas, filaria antigen test strips (FTS) are used, and in Brugia malayi areas, antibody test kits (Filaria DIAG RAPID) are used. Positive cases are confirmed by thick blood film (TBF) and polymerase chain reaction (PCR). Vector surveys for mosquito species identification and dissection for microfilaria (Mf)/filarial larvae are done in 1% of IUs where human blood surveys are conducted. Human blood surveys using FTS are conducted among migrants in five provinces. Surveillance of cats is done in areas that previously recorded > 1.0% Mf rate among cats. Morbidity management and disability prevention (MMDP) are done every 2 years in LF-endemic areas where chronic disease patients reside. Results From 2018 to 2022, in a total of 357 IUs in 11 provinces, human blood surveys were conducted in 145 IUs (41%) with an average population coverage of 81%. A total of 22,468 FTS and 27,741 FilariaDIAG RAPID were performed. 27 cases were detected: 3 cases of W. bancrofti in Kanchanaburi province and 24 cases of B. malayi in Narathiwat province. 4 cases of W. bancrofti were detected in two provinces through routine public health surveillance. Vector surveys in 47 IUs detected B. malayi Mf filarial larvae only in Narathiwat province. Chronic LF patients reduced from 114 in 2017 to 76 in 2022. Surveys among 7633 unregistered migrants yielded 12 cases of W. bancrofti. Mf rate among cats in Narathiwat province declined from 1.9% in 2018 to 0.7% in 2022. MMDP assessments revealed gaps in healthcare provider's management of chronic cases due to staff turnover. Conclusions In 2022, after 5 years of PVS, Thailand re-surveyed 41% of its previously endemic IUs and demonstrated ongoing transmission in only one province of Narathiwat, where Mf prevalence is below the WHO provisional transmission threshold of 1%. This study highlights the importance of continued disease surveillance measures and vigilance among health care providers in LF receptive areas. Graphical Abstract